Debt Covenants and Accounting Manipulation - Laux, Volker (The Accounting Review, 2022)
ABSTRACT This paper studies the effects of allocating control rights to lenders via debt covenants when managers can sometimes misreport the accounting information on which the covenants are based. When contract renegotiation is exogenously prohibited, including a covenant in the contract is ex ante optimal because it increases both the probability that poor projects are liquidated and the manager's effort incentive. When the parties can renegotiate the contract, the results can flip: granting the lender more control can lead to less frequent liquidations of low-quality projects and lower managerial effort incentives and thereby reduce the manager's ex ante payoff. The key behind these results is not the manager's incentive to misreport per se, but her desire to take subsequent actions that conceal the misreporting. The model generates predictions regarding the determinants of accounting-based covenants, and the effects of covenants on misreporting, managerial effort, the frequency of liquidations, and firm value. JEL Classifications: D23; D86; G32; G34; M41.